2020
DOI: 10.1038/s41598-020-78010-0
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional magnetization textures and domain-wall pinning in Sm–Co magnets

Abstract: Some of the best-performing high-temperature magnets are Sm–Co-based alloys with a microstructure that comprises an $$\hbox {Sm}_2\hbox {Co}_{17}$$ Sm 2 Co 17 matrix and magnetically hard $$\hbox {SmCo}_5$$ SmCo 5 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…All hysteresis loops have a shape typical for Sm(Co,Fe,Cu,Zr) z magnets, which does not change with temperature, as demonstrated for RT in Figure 6a and for 400 • C in Figure 6b. When the external magnetic field is applied in the opposite direction to demagnetize the remanent state, there is an initial dip in the magnetization (between 0 and 0.5 T), hypothesized to be due to the Z phase reversing its magnetization before the rest of the magnet 26 . Figure 6c shows the temperature dependence of the saturation magnetization (solid symbols) and remanence (hollow symbols) for all three samples.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All hysteresis loops have a shape typical for Sm(Co,Fe,Cu,Zr) z magnets, which does not change with temperature, as demonstrated for RT in Figure 6a and for 400 • C in Figure 6b. When the external magnetic field is applied in the opposite direction to demagnetize the remanent state, there is an initial dip in the magnetization (between 0 and 0.5 T), hypothesized to be due to the Z phase reversing its magnetization before the rest of the magnet 26 . Figure 6c shows the temperature dependence of the saturation magnetization (solid symbols) and remanence (hollow symbols) for all three samples.…”
Section: Resultsmentioning
confidence: 99%
“…However, the magnetic properties of the lamellar Z phase are not well studied, because they differ from their bulk values. A recent study showed that the Z phase has an insignificant magnetic anisotropy compared to the other two phases, and proposed that increasing the thickness of the Z phase would decrease the coercivity of the magnet 26 . Furthermore, the size of the Sm 2 Co 17 cells affects the coercivity and the arXiv:2101.12076v1 [cond-mat.mtrl-sci] 28 Jan 2021 remanence, because it determines the chemical composition of the cell walls 27 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] However, scientific interest alone provides sufficient reason for imaging these types of spatial variation. The spatial variations of order parameter could arise in any samples with structural/chemical inhomogeneity, [6,7] in large samples due to the formation of ferroic domains, [1,8] in small samples due to defects and boundaries, [9] and in thin-film multilayers that support topological defects of…”
Section: Imaging Ferroic Inhomogeneitymentioning
confidence: 99%
“…[ 1–5 ] However, scientific interest alone provides sufficient reason for imaging these types of spatial variation. The spatial variations of order parameter could arise in any samples with structural/chemical inhomogeneity, [ 6,7 ] in large samples due to the formation of ferroic domains, [ 1,8 ] in small samples due to defects and boundaries, [ 9 ] and in thin‐film multilayers that support topological defects of magnetic [ 10–12 ] and polar [ 13,14 ] order. Topological defects include skyrmions and vortices (5–100 nm in diameter), which can be electrically/magnetically manipulated, and used to carry topologically protected information in memory and logic devices.…”
Section: Imaging Ferroic Inhomogeneitymentioning
confidence: 99%